Analysis of Sales Budgeting Process in Fox Harris Hotel Jimbaran Beach - N K A M P Dewi; I N Sugiarta; D P Suciwati (Jurusan Akuntansi Politeknik Negeri Bali, 2020)
This study aims to describe sales budget preparation process at Fox Harris Hotel Jimbaran Beach. The preparation of the sales budget uses a free hand method by sales forecasting with intuition so that unfavorable variance may occur. Budget reports made by Revenue Manager are not based on accurate analysis. The purpose of this research is to learn how to arrange a sales budget at Fox Harris Hotel Jimbaran Beach. This research method uses quantitative and qualitative descriptive analysis technique. Quantitative analysis technique by calculating standard errors in the preparation of the budget and analysis of the variance of the sales budget on the budget implementation. The data in this study are primary and secondary obtained from interviews, documentation and observation. The result of the study shows that the right method in preparing the sale budget in Fox Harris Hotel Jimbaran Beach is a quadratic method. Difference in the sales budget due to the difference in the quantity and the difference in price.